Conjunctival squamous cell cancer - (:unkn) unknown (My University, 2002)
With advancing age immobile amelanotic conjunctival lesions of the interpalpebral area may often be seen. Considering these lesions, we should think of papilloma, leukoplaki and also conjunctiva cancer. In this case report we present an 80-year-old patient who was admitted to our clinic with the complaint of a mass in her right eye.
Keywords: Conjunctival cancer; Differential diagnosis